Selenium Accumulation Characteristics and Biofortification Potentiality in Turnip (Brassica rapa var. rapa) Supplied with Selenite or Selenate - Li, Xiong; Wu, Yuansheng; Li, Boqun; Yang, Yonghong; Yang, Yongping (Frontiers in Plant Science, 2018)
Selenium (Se) is an essential trace element for humans. About 70% of the regions in China, including most of the Tibetan Plateau, are faced with Se deficiency problems. Turnip is mainly distributed around the Tibetan Plateau and is one of the few local crops. In the present study, we compared the absorption and translocation differences of Se (Ⅳ) selenite and Se (Ⅵ) selenate in turnip. The results showed that Se treatment, either by soil addition (0.2–2 mg Se kg-1 dry soil) or by foliar spraying (50–200 mg L-1 Se), could significantly increase the Se concentrations in turnips, and 0.5 mg Se (Ⅳ) or Se (Ⅵ) kg-1 dry matter in soils could improve the biomasses of turnips. Moreover, turnip absorbed significantly more Se (Ⅵ) than Se (Ⅳ) at the same concentration and also transferred much more Se (Ⅵ) from roots to leaves. Based on the Se concentrations, as well as the bioconcentration factors and translocation coefficients, we considered that turnip might be a potential Se indicator plants. Subsequently, we estimated the daily Se intake for adults based on the Se concentrations in turnip roots. The results indicated that Se (Ⅳ) should be more suitable as artificial Se fertilizer for turnips, although the levels found in most samples in this study could cause selenosis to humans. In addition, we also estimated the optimum and maximum Se concentrations for treating turnips based on the linear relations between Se concentrations in turnip roots and Se treatment concentrations. The results provided preliminary and useful information about Se biofortification in turnips.